Analysis the Components of SNOW 3G and ZUC Ciphers in Mobile Systems - Fadhil Jasim, Khalid; Fakhri Al-Shaikhli, Imad (International Journal of Engineering and Technology, 2018)
The SNOW 3G and ZUC ciphers algorithms are classified as stream ciphers, used as confidentiality algorithms in third and fourth generations of Mobile Technologies (3G-UMTS and 4G- LTE). This research, focused on analyzing and evaluating randomness properties of various components of SNOW 3G and ZUC stream ciphers. Software programs of these ciphers and NIST (SP 800-22) tests adopted to assess the randomness properties. Many experiments conducted on output sequences of SNOW 3G and ZUC ciphers components. Practical experiments results confirmed that all SNOW 3G main components passed NIST tests. However, some components of ZUC Cipher passed NIST randomness tests, while significant components failed in NIST tests. Weaknesses pinpointed in randomness properties of ZUC cipher may be exploited by statistical cryptanalysis attacks, due to certain patterns appeared in the output sequences of failed ZUC Cipher components.Â Â